Analysis of Traffic Characteristics Based on Multi-Source Data – A Case Study of Jinan - Boqi LV; Zhenhua MOU; Qingbin WANG; Jiangshan PAN; Yongming WANG; Yuanxi ZHENG (Promet (Zagreb))
With the acceleration of urbanisation, the uneven distribution of educational resources has led to many children’s school choices, which has increased their school time and occupied a lot of rest time. Taking the Lixia District of Jinan City, China as an example, this paper uses the Thiessen polygon to delineate the scope of school districts, introduces the actual selection weight of children based on the OD data of students, and combines the 4 × 1,767 × 62 data obtained by Gaode API platform to construct the actual and school district accessibility model to study the accessibility and traffic fairness of families with different incomes in the process of school connection. The study identifies disparities in accessibility and traffic equity among income groups, with high-income families experiencing longer school commutes due to school choice behaviours. Compared with the actual general education, the difference in household income in the school district has a greater impact on traffic inequity. Therefore, reasonable school choice can reduce the difference in traffic accessibility between families.